2014
DOI: 10.1002/anie.201403638
|View full text |Cite
|
Sign up to set email alerts
|

Antifreezes Act as Catalysts for Methane Hydrate Formation from Ice

Abstract: Contrary to the thermodynamic inhibiting effect of methanol on methane hydrate formation from aqueous phases, hydrate forms quickly at high yield by exposing frozen water-methanol mixtures with methanol concentrations ranging from 0.6-10 wt% to methane gas at pressures from 125 bars at 253 K. Formation rates are some two orders of magnitude greater than those obtained for samples without methanol and conversion of ice is essentially complete. Ammonia has a similar catalytic effect when used in concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 35 publications
9
51
0
Order By: Relevance
“…Experimentally, hydrate formation from ice is a two-stage process with a relatively fast conversion of the ice surface [42][43][44]34] and a much slower process for bulk ice. Catalysts that interrupt surface hydrogen bonding can speed up this process by orders of magnitude [45].…”
Section: Nucleationmentioning
confidence: 99%
“…Experimentally, hydrate formation from ice is a two-stage process with a relatively fast conversion of the ice surface [42][43][44]34] and a much slower process for bulk ice. Catalysts that interrupt surface hydrogen bonding can speed up this process by orders of magnitude [45].…”
Section: Nucleationmentioning
confidence: 99%
“…This was experimentally observed in our recent work. 27 Adding methane to empty small cages of the sI hydrates increases the lattice constant. However, the clathrate hydrates with methane in the small cages have smaller lattice constants than analogous clathrate hydrates with NH 3 or CH 3 OH in the small cages.…”
Section: Journal Of Chemical and Engineering Datamentioning
confidence: 99%
“…A mono-ethylene glycol (MEG) aqueous solution system has been also investigated as a comparison with the silica system, because it is reported that MEG may promote the hydrate formation kinetics. 25,26 In attempting to understand the formation process of hydrate phase, we formed mixed hydrate from a gas mixture (methane, ethane, and propane) and measured the amount of consumed gas during the formation process. In situ Raman spectroscopy was used to monitor the inclusion process of gas molecules in hydrate cages.…”
Section: Introductionmentioning
confidence: 99%